2015
DOI: 10.14735/amko2015112
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the Management of Clinical Stage I Nonseminomatous Germ Cell Testicular Cancer

Abstract: SummarySurveillance after orchiectomy alone has become popular in the management of clinical stage I of nonseminomatous germ cell testicular tumors (CSI NSGCTT). Eff orts to identify patients at high-risk of relapse led to a search for risk factors in CSI NSGCTT. The aim of the current study was to analyze long-term experiences with risk-adapted therapeutic approaches (active surveillance and adjuvant chemotherapy). From 1/ 1992 to 2/ 2015, a total of 454 CSI NSGCTT patients were included in the study and stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The question whether two cycles of carboplatin result in lower relapse rates compared to the one course regimen has not been systematically evaluated. However, three studies indicated relapse rates of > 10% ensuing from the one course regimen [ 37 , 40 , 41 ], while all single-arm studies employing the two-course regimen reported relapse rates < 5%. On the other hand, a worse outcome was observed in cases relapsing after two cycles of carboplatin, although some selection bias must be considered in that retrospective study [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The question whether two cycles of carboplatin result in lower relapse rates compared to the one course regimen has not been systematically evaluated. However, three studies indicated relapse rates of > 10% ensuing from the one course regimen [ 37 , 40 , 41 ], while all single-arm studies employing the two-course regimen reported relapse rates < 5%. On the other hand, a worse outcome was observed in cases relapsing after two cycles of carboplatin, although some selection bias must be considered in that retrospective study [ 42 ].…”
Section: Discussionmentioning
confidence: 99%